Genome-wide identification and characterization of indeterminate domain (IDD) gene family in sunflower (Helianthus annuus) (Plant Bulletin, 2025)
Indeterminate Domain (IDD) represents a large and evolutionary conserved gene family in plants playing critical roles in growth and seed development. Despite its agronomic significance as oilseed crop, a systematic analysis of IDD gene family is sunflower (Helianthus annus) has been lacking. In this work, 78 IDD genes were identified across six species, including 21 in H. annus. Phylogenetic analysis grouped IDDs genes into four distinct sub-groups, showing a closer evolutionary relationship between H. annus, Theobroma cacao, Zea mays, Arabidopsis thaliana, Physcomitrella patens, Selaginella moellendorffii and Oryza sativa. Gene structure analysis showed that most HaIDD genes have two intron and three exons. Conserved domain analysis identified ten different motifs related to abiotic stress tolerance. Sequence logo analysis further confirmed the high conservation of IDD family in H. annus and A. thaliana. The intracellular localization prediction showed that all HaIDD proteins were present inside nucleus. Upstream region analysis showed the existence of cis-acting element associated to abiotic stress responses, proposing a probable role for HaIDDs in stress tolerance sunflower breeding. The selection pressure was calculated by Ka/Ks ratio which indicated purifying selection because the value significantly less than one. Gene expression analysis demonstrated differential expression of HaIDDs across leaves, stamen bract, pollen, pistil, corolla, ligule, ovary and seeds. Especially, HaIDD3 showed higher expression in leaves and seeds suggesting potential role in photosynthesis and seed development. Overall, these results indicate that HaIDDs are mainly involved governing plant developmental processes and abiotic stress responses in sunflower.
Keywords: Helianthus annuus; transcription factors; phylogenetic analysis; semi qPCR; Indeterminate Domain